Vinyl chloride-silicone graft copolymer and its manufacturing method
The vinyl chloride-silicone graft copolymer addresses the challenge of combining the properties of silicone and PVC resins by grafting organopolysiloxane and vinyl chloride, resulting in a resin with enhanced sliding, water repellency, alcohol resistance, substrate adhesion, and transparency.
Patent Information
- Application Number
- JP2024001794
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-01-10
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2044-01-10
AI Technical Summary
Existing technologies face challenges in combining the properties of silicone-based resins and polyvinyl chloride (PVC) resins, particularly in achieving sliding properties, water repellency, alcohol resistance, substrate adhesion, and transparency in a single resin.
A vinyl chloride-silicone graft copolymer is developed by grafting organopolysiloxane and vinyl chloride in specific mass ratios, allowing for the combination of the beneficial properties of both resin types.
The resulting vinyl chloride-silicone graft copolymer exhibits sliding properties, water repellency, alcohol resistance, substrate adhesion, and transparency, making it suitable for various applications such as coating agents, adhesives, and paints.
Smart Images

Figure 0007667889000001 
Figure 0007667889000002 
Figure 0007667889000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a graft copolymer of organopolysiloxane and vinyl chloride and a method for producing the same. More specifically, the present invention relates to a vinyl chloride-silicone graft copolymer that has sliding properties, water repellency, alcohol resistance, adhesion to substrates, and transparency, and a method for producing the same. [Background technology]
[0002] Silicone-based resins have been known as resins capable of imparting slidability to substrates, but when used alone, silicone-based resins have problems such as poor adhesion to substrates.
[0003] Therefore, a method has been used in which a silicone resin is copolymerized with another monomer such as an acrylic resin, a urethane resin, or a vinyl acetate resin. Copolymers such as acrylic silicone and urethane silicone can impart the advantages of silicone resin, such as weather resistance, heat resistance, cold resistance, water repellency, gas permeability, and sliding properties, to the properties of acrylic resin and urethane resin.
[0004] For example, Patent Document 1 (JP 2020-90563 A) discloses a silicone acrylic graft copolymer resin having sliding properties and a method for producing the same. Furthermore, Patent Document 2 (JP 2022-131528 A) discloses a vinyl acetate-silicone copolymer resin having sliding properties, substrate adhesion, and organic solvent solubility and a method for producing the same.
[0005] On the other hand, it is known that vinyl chloride resin is also used after being copolymerized with another monomer. For example, vinyl chloride-vinyl acetate copolymer resin, in which vinyl chloride and vinyl acetate are copolymerized, can be mentioned. Patent Document 3 (JP Patent Publication 2001-114839 A) and the like disclose vinyl chloride-vinyl acetate copolymer resin and a method for producing the same, and it is known that the use of the same in base materials such as ink materials and receiving layers enhances color development and adhesion.
[0006] It was known that silicone resins or vinyl chloride resins could be copolymerized by reacting each with a different monomer, but since vinyl chloride and organopolysiloxane (silicone resin) are inherently incompatible, there had been almost no attempt to copolymerize the two. Furthermore, it was not thought that copolymerizing silicone and vinyl chloride would produce a resin that utilized the properties of both.
[0007] Patent Document 4 (JP Patent Publication 59-166520 A) discloses that a resin obtained by graft polymerizing silicone onto polyvinyl chloride resin has good oxygen permeability, and the resin has been considered for use in the field of packaging for fresh food and in medical blood bags. However, the roll-kneaded product is not very practical for use in these applications in the form of a sheet, and there is room for improvement.
[0008] In addition, Patent Document 5 (JP Patent Publication 07-102146 A) discloses that the use of a block copolymer resin consisting of vinyl chloride and siloxane blocks improves the peelability during calendar roll processing. Patent Document 6 (JP Patent Publication 09-255705 A) discloses the polymerization of vinyl chloride in the presence of a copolymer resin of siloxane and acrylic. These are used as additives during the production of vinyl chloride resin, and little research has been conducted on vinyl chloride-silicone copolymer resins.
[0009] Furthermore, a method of obtaining a coating agent by mixing a silicone resin emulsion and a vinyl chloride resin emulsion has been considered, but the silicone component bleeds out in the mixture, making it difficult to obtain the desired performance, leaving room for improvement. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2020-90563 A [Patent Document 2] JP 2022-131528 A [Patent Document 3] JP 2001-114839 A [Patent Document 4] Japanese Patent Application Publication No. 59-166520 [Patent Document 5] Japanese Patent Application Publication No. 07-102146 [Patent Document 6] Japanese Patent Application Publication No. 09-255705 Summary of the Invention [Problem to be solved by the invention]
[0011] Therefore, an object of the present invention is to provide a vinyl chloride-silicone graft copolymer that has sliding properties, water repellency, alcohol resistance, adhesion to substrates, and transparency. [Means for solving the problem]
[0012] As a result of intensive research conducted by the inventors in order to achieve the above-mentioned object, they discovered that a vinyl chloride-silicone graft copolymer obtained by graft copolymerization of the following (A) organopolysiloxane and (B) vinyl chloride has excellent sliding properties, water repellency, alcohol resistance, adhesion to substrates, and transparency, and thus completed the present invention.
[0013] That is, the present invention provides the following vinyl chloride-silicone graft copolymer, a method for producing the same, and a composition and emulsion of the graft copolymer.
[0014] [1] A vinyl chloride-silicone graft copolymer which is a graft copolymer of (A) an organopolysiloxane represented by the following formula (1) and (B) vinyl chloride, wherein the mass ratio of said (A) organopolysiloxane to said (B) vinyl chloride is (A):(B)=5:95 to 95:5. [ka] (In formula (1), R 1are the same or different substituted or unsubstituted monovalent hydrocarbon groups having 1 to 20 carbon atoms, R 2 is a radical reactive functional group. X is the same or different, substituted or unsubstituted, monovalent hydrocarbon group having 1 to 20 carbon atoms, alkoxy group having 1 to 20 carbon atoms, or hydroxyl group. Y is X or -[O-Si(X) 2 ] d -X is the same or a different group. Z is an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, or a hydroxyl group. a is a number from 0 to 10,000, b is a number from 100 to 10,000, c is a number from 0.0001 to 100, and d is a number from 1 to 1,000. [2] A method for producing a vinyl chloride-silicone graft copolymer, comprising the step of polymerizing (A) an organopolysiloxane represented by the following formula (1) with (B) vinyl chloride in a mass ratio of (A):(B) = 5:95 to 95:5: [ka] (In formula (1), R 1 are the same or different substituted or unsubstituted monovalent hydrocarbon groups having 1 to 20 carbon atoms, R 2 is a radical reactive functional group. X is the same or different, substituted or unsubstituted, monovalent hydrocarbon group having 1 to 20 carbon atoms, alkoxy group having 1 to 20 carbon atoms, or hydroxyl group. Y is X or -[O-Si(X) 2 ] d -X is the same or a different group. Z is an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, or a hydroxyl group. a is a number from 0 to 10,000, b is a number from 100 to 10,000, c is a number from 0.0001 to 100, and d is a number from 1 to 1,000. [3] A composition comprising the vinyl chloride-silicone graft copolymer according to [1] in an amount of 10 to 60% by mass in terms of solid content based on the total mass of the composition. [4] An emulsion of the vinyl chloride-silicone graft copolymer described in [1]. Effect of the Invention
[0015] The vinyl chloride-silicone graft copolymer of the present invention has good sliding properties, water repellency, alcohol resistance, adhesion to substrates, and transparency, and therefore compositions containing the vinyl chloride-silicone graft copolymer of the present invention are suitable for use as coating agents for various substrates, adhesives, exterior and interior paints for structures and building materials, and cosmetics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Vinyl chloride-silicone graft copolymer The present invention relates to a vinyl chloride-silicone graft copolymer obtained by graft copolymerization of (A) an organopolysiloxane and (B) vinyl chloride.
[0017] The organopolysiloxane (A) in the present invention is represented by the following formula (1). [ka] (In formula (1), R 1 are the same or different substituted or unsubstituted monovalent hydrocarbon groups having 1 to 20 carbon atoms, R 2 is a radical reactive functional group. X is the same or different, substituted or unsubstituted, monovalent hydrocarbon group having 1 to 20 carbon atoms, alkoxy group having 1 to 20 carbon atoms, or hydroxyl group. Y is X or -[O-Si(X) 2 ] d -X is the same or different group. Z is an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, or a hydroxyl group. a is a number from 0 to 10,000, b is a number from 100 to 10,000, c is a number from 0.0001 to 100, and d is a number from 1 to 1,000.
[0018] Here, R 1are the same or different substituted or unsubstituted monovalent hydrocarbon groups having 1 to 20 carbon atoms, and specifically, examples of such groups include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, dodecyl, tetradecyl, hexadecyl, and octadecyl groups, cycloalkyl groups such as cyclopentyl, cyclohexyl, and cycloheptyl groups, alkenyl groups such as vinyl and allyl groups, aryl groups such as phenyl, tolyl, and naphthyl groups, vinyl fluorine, and the like. Examples of the alkyl group include alkenylaryl groups such as a phenyl group, aralkyl groups such as a benzyl group, a phenylethyl group, and a phenylpropyl group, and alkenylaralkyl groups such as a vinylbenzyl group and a vinylphenylpropyl group, as well as groups in which some or all of the hydrogen atoms are substituted with halogen atoms such as fluorine, bromine, and chlorine, acryloxy groups, methacryloxy groups, carboxyl groups, alkoxy groups, alkenyloxy groups, amino groups, and alkyl, alkoxy, or (meth)acryloxy-substituted amino groups. 1 is preferably a methyl group.
[0019] R 2 is a radical reactive functional group, and is preferably a mercapto group or an alkyl group having 1 to 8 carbon atoms substituted with an ethylenic double bond-containing group. Specifically, it is a vinyl group, a styryl group, a mercapto group, an acryloxy group, or an alkyl group having 1 to 8 carbon atoms substituted with a methacryloxy group. Examples of the functional group include a vinyl group, a styryl group, an octenyl group, a methacryloxyoctyl group, a mercaptopropyl group, an acryloxypropyl group, a methacryloxypropyl group, and a methacryloxyoctylvinyl group.
[0020] X is the same or different, a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, or a hydroxyl group. The unsubstituted or substituted monovalent hydrocarbon group having 1 to 20 carbon atoms is preferably R 1Examples of the alkoxy group having 1 to 20 carbon atoms include a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a hexyloxy group, a heptyloxy group, an octyloxy group, a decyloxy group, a tetradecyloxy group, etc. Among these, a hydroxyl group, a methyl group, a butyl group, and a phenyl group are preferred.
[0021] Y is X or -[O-Si(X) 2 ] d -X is the same or different group. Examples of X include the same groups as those exemplified above.
[0022] Z is an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, or a hydroxyl group, and is preferably a hydroxyl group or a methyl group.
[0023] a is a number from 0 to 10,000, preferably a number from 0 to 1,000, and more preferably a number from 0 to 200. When constituting a units, the lowest limit is preferably 0.5. If a is more than 10,000, the strength of the film obtained when the composition containing component (A) is used as a coating film may be insufficient. b is a number from 100 to 10,000, and preferably a number from 1,000 to 5,000. If b is less than 100, the coating may have poor flexibility, and if it is more than 10,000, the tear strength may decrease. The value c is a number from 0.0001 to 100, and if it exceeds 100, the sliding effect may not be exhibited. Here, c / (a+b+c)×100 is preferably 0.0001 to 10, and more preferably 0.001 to 10. d is a number from 1 to 1,000, and preferably a number from 1 to 200.
[0024] The organopolysiloxane represented by the above formula (1) is preferably used in the form of an emulsion, and may be a commercially available product or may be synthesized. When synthesizing, it can be synthesized by a known emulsion polymerization method, for example, by emulsifying and dispersing a cyclic organosiloxane or an α,ω-dihydroxysiloxane oligomer, an α,ω-dialkoxysiloxane oligomer, an alkoxysilane, or the like, and a silane coupling agent represented by the following formula (2) in water using an anionic surfactant, and then adding a polymerization catalyst such as an acid as necessary to carry out a polymerization reaction, thereby easily synthesizing it. The cyclic organosiloxane may have a fluorine atom, a (meth)acryloxy group, a carboxyl group, a hydroxyl group, or an amino group. [ka] (In formula (2), R 3 R is a radical reactive functional group. In particular, it is an acryloxy group, a methacryloxy group, a vinyl group, or a mercapto-substituted alkyl group having 1 to 8 carbon atoms, or a styryl group or a vinyl group. 4 is an alkyl group or a hydroxyl group having 1 to 4 carbon atoms, and R 5 is an alkyl group having 1 to 4 carbon atoms, e is 2 or 3, f is 0 or 1, and e+f is 2 or 3.
[0025] Examples of the cyclic organosiloxane include hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), dodecamethylcyclohexasiloxane (D6), 1,1-diethylhexamethylcyclotetrasiloxane, phenylheptamethylcyclotetrasiloxane, 1,1-diphenylhexamethylcyclotetrasiloxane, 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, 1,3,5,7-tetracyclohexyltetramethylcyclotetrasiloxane, tris(3,3,3-trifluoropropyl)trimethylcyclotrisiloxane, 1,3,5,7-tetra(3-methacryloxypropyl)tetramethylsiloxane, and the like. Examples of the tetrasiloxane include chlorotetrasiloxane, 1,3,5,7-tetra(3-acryloxypropyl)tetramethylcyclotetrasiloxane, 1,3,5,7-tetra(3-carboxypropyl)tetramethylcyclotetrasiloxane, 1,3,5,7-tetra(3-vinyloxypropyl)tetramethylcyclotetrasiloxane, 1,3,5,7-tetra(p-vinylphenyl)tetramethylcyclotetrasiloxane, 1,3,5,7-tetra[3-(p-vinylphenyl)propyl]tetramethylcyclotetrasiloxane, 1,3,5,7-tetra(N-acryloyl-N-methyl-3-aminopropyl)tetramethylcyclotetrasiloxane, and 1,3,5,7-tetra(N,N-bis(lauroyl)-3-aminopropyl)tetramethylcyclotetrasiloxane. Octamethylcyclotetrasiloxane and decamethylcyclopentasiloxane are preferably used.
[0026] Specific examples of the silane coupling agent include vinyl silanes such as vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tripropoxy silane, vinyl triisopropoxy silane, vinyl methyl dimethoxy silane, and vinyl methyl diethoxy silane; γ-(meth)acryloxypropyl trimethoxy silane, γ-(meth)acryloxypropyl triethoxy silane, γ-(meth)acryloxypropyl tripropoxy silane, γ-(meth)acryloxypropyl triisopropoxy silane, and γ-(meth)acryloxypropyl tributoxy silane. Examples of the silane include acrylic silanes such as γ-(meth)acryloxypropylmethyldimethoxysilane, γ-(meth)acryloxypropylmethyldiethoxysilane, γ-(meth)acryloxypropylmethyldipropoxysilane, γ-(meth)acryloxypropylmethyldiisopropoxysilane, and γ-(meth)acryloxypropylmethyldibutoxysilane; mercaptosilanes such as γ-mercaptopropylmethyldimethoxysilane and γ-mercaptopropyltrimethoxysilane; and styrylsilanes such as styryltrimethoxysilane. In addition, oligomers obtained by condensation polymerization of these may be more preferable because they suppress the generation of alcohol. Here, (meth)acryloxy refers to acryloxy or methacryloxy. The silane coupling agent is preferably used in an amount of 0.01 to 20 parts by mass, and more preferably 0.01 to 5 parts by mass, per 100 parts by mass of cyclic organosiloxane, α,ω-dihydroxysiloxane oligomer, α,ω-dialkoxysiloxane oligomer, or alkoxysilane.
[0027] By copolymerizing a cyclic organosiloxane, an α,ω-dihydroxysiloxane oligomer, an α,ω-dialkoxysiloxane oligomer, or an alkoxysilane with a silane coupling agent, a unit having a repeat number c in the above formula (1), ([Si(R 2 )(Z)O]), which allows graft polymerization of (B) vinyl chloride.
[0028] As the polymerization catalyst, a known polymerization catalyst may be used. Among them, a strong acid is preferable, and examples thereof include hydrochloric acid, sulfuric acid, dodecylbenzenesulfonic acid, citric acid, lactic acid, and ascorbic acid. Dodecylbenzenesulfonic acid having a surface activity is preferable. The amount of the acid catalyst used is preferably 0.01 to 10 parts by mass, and more preferably 0.2 to 2 parts by mass, per 100 parts by mass of the cyclic organosiloxane, α,ω-dihydroxysiloxane oligomer, α,ω-dialkoxysiloxane oligomer, or alkoxysilane.
[0029] As the anionic surfactant, preferred are sodium lauryl sulfate, sodium laureth sulfate, N-acylamino acid salts, N-acyltaurate salts, aliphatic soaps, alkyl phosphates, sodium lauroyl methyl taurate, sodium myristoyl methyl taurate, etc. More preferred are N-acylamino acid salts, N-acyltaurate salts, aliphatic soaps, alkyl phosphates, sodium lauroyl methyl taurate, sodium myristoyl methyl taurate, and particularly preferred are sodium lauroyl methyl taurate, sodium myristoyl methyl taurate, and sodium lauryl sulfate.
[0030] The amount of the anionic surfactant used is preferably 0.1 to 20 parts by mass, and more preferably 0.5 to 10 parts by mass, per 100 parts by mass of the cyclic organosiloxane, α,ω-dihydroxysiloxane oligomer, α,ω-dialkoxysiloxane oligomer, or alkoxysilane.
[0031] The polymerization temperature is preferably 50 to 75° C., and the polymerization time is preferably 10 hours or more, more preferably 15 hours or more. Furthermore, it is particularly preferable to age the mixture after polymerization at 5 to 30° C. for 10 hours or more.
[0032] After the polymerization reaction is completed, the reaction mixture may be neutralized to a pH of 2.5 to 14, preferably 4 to 11, using a neutralizing agent (eg, a 10% aqueous sodium carbonate solution).
[0033] The weight average molecular weight (Mw) of the (A) organopolysiloxane, as determined by viscosity measurement, is preferably from 10,000 to 1,000,000, and more preferably from 100,000 to 500,000, from the viewpoint of sliding effect.
[0034] Here, the weight average molecular weight (Mw) of an organopolysiloxane determined by viscosity measurement is calculated from the specific viscosity ηsp (25° C.) of a toluene solution of the organopolysiloxane at a concentration of 1 g / 100 ml. ηsp=(η / η0)-1 (η0: viscosity of toluene η: viscosity of solution) ηsp=[η]+0.3[η] 2 [η]=0.215×10 -4 M 0.65 Specifically, 20 g of the emulsion is mixed with 20 g of IPA (isopropyl alcohol), the emulsion is broken, the IPA is discarded, and the remaining rubber-like organopolysiloxane is dried overnight at 60°C. This is made into a toluene solution of organopolysiloxane with a concentration of 1 g / 100 ml, and the viscosity is measured at 25°C using an Ubbelohde viscometer. The molecular weight can be calculated by substituting the viscosity into the above formula (References: Nakamuta, Nikka, 77 858
[1956] , Doklady Akad. Nauk. USSR 89 65
[1953] ).
[0035] Manufacturing method The vinyl chloride-silicone graft copolymer of the present invention can be obtained by graft polymerization of (A) an organopolysiloxane and (B) vinyl chloride.
[0036] The method for producing the vinyl chloride-silicone graft copolymer of the present invention comprises the step of graft polymerizing the organopolysiloxane of formula (1) (component (A)) with vinyl chloride (component (B)) in a mass ratio (mass ratio of the organopolysiloxane of formula (1) to the vinyl chloride unit) of 5:95 to 95:5, preferably 20:80 to 85:15. If the ratio of the organopolysiloxane component of formula (1) is less than the above 5, the sliding effect may not be achieved.
[0037] Radical initiators used in the production of the vinyl chloride-silicone graft copolymer of the present invention include persulfates such as potassium persulfate and ammonium persulfate, hydrogen persulfate water, t-butyl hydroperoxide, and hydrogen peroxide. If necessary, redox compounds can be used in combination with reducing agents such as sodium sulfite, Rongalit, L-ascorbic acid, tartaric acid, sugars, and amines. The amount of the radical initiator used is preferably from 0.1 to 5 mass %, more preferably from 0.5 to 3 mass %, of the vinyl chloride (B).
[0038] The polymerization temperature of component (B) relative to component (A) is preferably 25 to 85° C., more preferably 55 to 85° C. The polymerization time is preferably 2 to 20 hours, more preferably 3 to 10 hours.
[0039] Furthermore, a chain transfer agent can be added to adjust the molecular weight and polymerization rate of the polymer. Examples of the chain transfer agent include halogenated hydrocarbons such as chloroform and carbon tetrachloride, and mercaptans such as n-dodecyl mercaptan, tert-dodecyl mercaptan, and n-octyl mercaptan. The amount of the chain transfer agent used is preferably 0.1 to 1 part by mass, and more preferably 0.3 to 0.8 parts by mass, based on 100 parts by mass of the monomer.
[0040] The vinyl chloride-silicone graft copolymer obtained in this manner is a polymer in which the vinyl chloride, component (B), is randomly bonded to the organopolysiloxane, component (A), and is a polymer that is a mixture of various structures, making it impossible to directly identify the product by its structure or properties.
[0041] The method for producing the vinyl chloride-silicone graft copolymer of the present invention preferably comprises the step of emulsion polymerizing the organopolysiloxane of formula (1) (component (A)) and vinyl chloride (component (B)) in a mass ratio (mass ratio of the organopolysiloxane of formula (1) to vinyl chloride units) of 5:95 to 95:5, preferably 20:80 to 85:15. Although the surfactant contained in the organopolysiloxane emulsion is sufficient for graft polymerization, anionic surfactants such as sodium lauryl sulfate, sodium laureth sulfate, N-acylamino acid salts, N-acyltaurate salts, aliphatic soaps, and alkyl phosphates can be added to improve stability. Nonionic emulsifiers such as polyoxyethylene lauryl ether and polyoxyethylene tridecyl ether can also be added. When a surfactant is added, the amount used is preferably 0.1 to 5% by mass of (B) vinyl chloride.
[0042] The vinyl chloride-silicone graft copolymer preferably has a solid content of 25 to 40% by mass. The viscosity of the emulsion (25°C) is preferably 1 to 500 mPa·s, more preferably 1 to 200 mPa·s. The viscosity can be measured with a rotational viscometer. The average particle size of the emulsion is preferably 0.1 μm (100 nm) to 0.5 μm (500 nm). The average particle size is a value measured with a dynamic light scattering particle size distribution measuring device.
[0043] The vinyl chloride-silicone graft copolymer of the present invention can also be granulated from the emulsion and powdered by the following methods. These include freeze grinding, spray drying, air flow drying, etc., but spray drying is preferred from the viewpoint of productivity. The smaller the average particle size of the resulting powder particles, the better, with 1 to 50 μm being preferred, and 1 to 30 μm being more preferred. The particle sizes of the emulsion and powder can be measured as the cumulative mass average value D50 using a laser diffraction particle size measuring device.
[0044] By using the vinyl chloride-silicone graft copolymer (copolymer resin) of the present invention in combination with other resins, pigments, fillers, matting agents, antioxidants, UV absorbers, antifreeze agents, pH adjusters, preservatives, defoamers, antibacterial agents, antifungal agents, light stabilizers, antistatic agents, plasticizers, flame retardants, thickeners, surfactants and / or organic solvents (such as film-forming assistants), etc., compositions containing the vinyl chloride-silicone graft copolymer can be used in applications such as coating agents for various substrates such as synthetic resins, metals, glass, ceramics, gypsum, paper, wood, leather, lightweight concrete, lightweight aerated concrete, mortar, calcium silicate boards, slates, gypsum boards, etc.; adhesives; paint binders for exterior and interior use of structures and building materials, etc.; paper processing agents; fiber treatment agents; cosmetics, etc.
[0045] The composition containing the vinyl chloride-silicone graft copolymer of the present invention preferably contains the vinyl chloride-silicone graft copolymer in an amount of 10 to 60 mass %, more preferably 20 to 50 mass %, and particularly preferably 30 to 50 mass %, in terms of solids content relative to the mass of the entire composition.
[0046] In addition, when an organic solvent is mixed with the composition containing the vinyl chloride-silicone graft copolymer, examples of the organic solvent include aromatic hydrocarbons such as styrene, toluene, xylene, and ethylbenzene; aliphatic hydrocarbons such as hexane and cyclohexane; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ethers such as tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, and anisole; esters such as ethyl acetate, butyl acetate, propylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; cellosolves such as methyl cellosolve, ethyl cellosolve, and butyl cellosolve; alcohols such as methanol, ethanol, isopropanol, and n-butanol; nitriles such as acetonitrile, propionitrile, butyronitrile, and benzonitrile; amide compounds such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone; chloroform; and dimethyl sulfoxide. The organic solvents may be used alone or in combination.
[0047] The composition containing the vinyl chloride-silicone graft copolymer of the present invention can be used as a coating agent. In this case, the coating agent can be obtained by mixing and dissolving the vinyl chloride-silicone graft copolymer and other components using a known mixing and preparation method such as a propeller stirrer, homogenizer, ball mill, or bead mill. When the coating agent is applied or immersed on one or both sides of a substrate such as glass or resin and then dried, it can impart sliding properties and substrate adhesion. EXAMPLES
[0048] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples. The molecular weights described below are weight average molecular weights (Mw) determined by viscosity measurement based on the specific viscosity of a toluene solution of organopolysiloxane at a concentration of 1 g / 100 ml. In the following examples, parts and % represent parts by mass and % by mass, respectively.
[0049] [Example 1] 1200g of octamethylcyclotetrasiloxane, 4.8g of γ-methacryloxypropylmethyldimethoxysilane, 12g of sodium lauryl sulfate dissolved in 108g of pure water, and 12g of dodecylbenzenesulfonic acid dissolved in 108g of pure water were charged into a 4L polyethylene beaker and emulsified uniformly using a homomixer. After that, 728g of water was gradually added to dilute the mixture and the mixture was stirred at a pressure of 300kgf / cm. 2 The emulsion was passed through a high-pressure homogenizer twice at 100°C to obtain a uniform white emulsion. This emulsion was transferred to a 2L glass flask equipped with a stirrer, thermometer, and reflux condenser, and polymerized at 55°C for 24 hours, after which it was aged at 15°C for 24 hours and neutralized to pH 7 with a 10% aqueous sodium carbonate solution. After drying at 105°C for 3 hours, the non-volatile content (solid content) of this emulsion was 44%, and the organopolysiloxane in the emulsion was in the form of a non-fluid soft gel. Based on the viscosity of the toluene solution, this emulsion (silicone composition) had a structure represented by the following formula (A) with a molecular weight of approximately 250,000. In formula (A), R 2 is a γ-methacryloxypropyl group. The structure of the organopolysiloxane obtained by the above polymerization reaction is 1 H-NMR (frequency 600 MHz, room temperature, number of accumulations 128) and 29 Si-NMR (frequency 60 MHz, room temperature, 5000 times accumulation) (instrument name: JNM-ECA600, measurement solvent: CDCl 3 ) was confirmed. [ka] 1207 g of the above emulsion was transferred to a polymerization vessel equipped with a stirrer, condenser, thermometer, and nitrogen gas inlet, and 59 g of vinyl chloride and ammonium persulfate were added and reacted at 60°C for 8 hours to graft copolymerize vinyl chloride onto the above silicone composition, yielding an emulsion of vinyl chloride-silicone graft copolymer with a non-volatile content of 30%. The obtained vinyl chloride-silicone graft copolymer was 2 Vinyl chloride is graphed on to The polymer was a vinyl chloride-silicone graft copolymer.
[0050] [Example 2] An emulsion of vinyl chloride-silicone graft copolymer with a non-volatile content of 30% was obtained in the same manner as in Example 1, except that the amount of vinyl chloride was changed to 132 g.
[0051] [Example 3] An emulsion of silicone-vinyl chloride graft copolymer with a non-volatile content of 30% was obtained in the same manner as in Example 1, except that the amount of vinyl chloride was changed to 226 g.
[0052] [Example 4] 1200g of octamethylcyclotetrasiloxane, 0.96g of γ-methacryloxypropylmethyldimethoxysilane, 12g of sodium lauryl sulfate dissolved in 108g of pure water, and 12g of dodecylbenzenesulfonic acid dissolved in 108g of pure water were charged into a 4L polyethylene beaker and emulsified uniformly using a homomixer. After that, 728g of water was gradually added to dilute the mixture and the mixture was stirred at a pressure of 300kgf / cm. 2 The emulsion was passed through a high-pressure homogenizer twice at 100°C to obtain a uniform white emulsion. This emulsion was transferred to a 2L glass flask equipped with a stirrer, thermometer, and reflux condenser, and polymerized at 55°C for 24 hours, after which it was aged at 15°C for 24 hours and neutralized to pH 7 with a 10% aqueous sodium carbonate solution. After drying at 105°C for 3 hours, the non-volatile content (solid content) of this emulsion was 45%, and the organopolysiloxane in the emulsion was in the form of a non-fluid soft gel. Based on the viscosity of the toluene solution, this emulsion (silicone composition) had a structure represented by the following formula (B) with a molecular weight of approximately 250,000. In formula (B), R 2 is a γ-methacryloxypropyl group. [ka] 1,198 g of the above emulsion was transferred to a polymerization vessel equipped with a stirrer, condenser, thermometer, and nitrogen gas inlet, and 231 g of vinyl chloride and ammonium persulfate were added and reacted at 60°C for 8 hours to graft copolymerize vinyl chloride onto the above silicone composition, yielding an emulsion of vinyl chloride-silicone graft copolymer with a non-volatile content of 30%. The obtained vinyl chloride-silicone graft copolymer was 2 Vinyl chloride is graphed on to The polymer was a vinyl chloride-silicone graft copolymer.
[0053] [Example 5] An emulsion of vinyl chloride-silicone graft copolymer with a non-volatile content of 30% was obtained in the same manner as in Example 1, except that the amount of vinyl chloride was changed to 528 g.
[0054] [Example 6] An emulsion of vinyl chloride-silicone graft copolymer with a non-volatile content of 30% was obtained in the same manner as in Example 1, except that the amount of vinyl chloride was changed to 1,232 g.
[0055] [Example 7] An emulsion of vinyl chloride-silicone graft copolymer with a non-volatile content of 30% was obtained in the same manner as in Example 1, except that the amount of vinyl chloride was changed to 4,752 g.
[0056] [Comparative Example 1] 1200g of octamethylcyclotetrasiloxane, 4.8g of γ-methacryloxypropylmethyldimethoxysilane, 12g of sodium lauryl sulfate dissolved in 108g of pure water, and 12g of dodecylbenzenesulfonic acid dissolved in 108g of pure water were charged into a 4L polyethylene beaker and emulsified uniformly using a homomixer. After that, 728g of water was gradually added to dilute the mixture and the mixture was stirred at a pressure of 300kgf / cm. 2The emulsion was passed through a high-pressure homogenizer twice at 100°C to obtain a uniform white emulsion. The emulsion was transferred to a 2L glass flask equipped with a stirrer, thermometer, and reflux condenser, and polymerized at 55°C for 24 hours, then aged at 15°C for 24 hours, and neutralized to pH 7 with a 10% aqueous sodium carbonate solution. After drying at 105°C for 3 hours, the non-volatile content (solid content) of the emulsion was 44%, and the organopolysiloxane in the emulsion was in the form of a non-fluid soft gel. Based on the viscosity of the toluene solution, the emulsion (silicone composition) had a structure represented by the above formula (A) with a molecular weight of about 250,000.
[0057] [Comparative Example 2] A polymerization vessel equipped with a stirrer, a condenser, a thermometer, and a nitrogen gas inlet was charged with 840 g of vinyl chloride, 16.8 g of 2-hydroxyethyl methacrylate, and potassium peroxodisulfate, and the reaction was carried out at 45°C for 30 hours to obtain an emulsion of a copolymer with a non-volatile content of 40%.
[0058] [Comparative Example 3] 1200g of octamethylcyclotetrasiloxane, 0.96g of γ-methacryloxypropylmethyldimethoxysilane, 12g of sodium lauryl sulfate dissolved in 108g of pure water, and 12g of dodecylbenzenesulfonic acid dissolved in 108g of pure water were charged into a 2L polyethylene beaker and emulsified uniformly using a homomixer. Then, 400g of water was gradually added to dilute the mixture and the mixture was stirred at a pressure of 300kgf / cm. 2 The emulsion was passed through a high-pressure homogenizer twice at 100°C to obtain a uniform white emulsion. The emulsion was transferred to a 2L glass flask equipped with a stirrer, thermometer, and reflux condenser, and polymerized at 55°C for 24 hours, then aged at 15°C for 24 hours, and neutralized to pH 7 with a 10% aqueous sodium carbonate solution. After drying at 105°C for 3 hours, the emulsion had a non-volatile content of 45%, and the organopolysiloxane in the emulsion was in the form of a non-fluid soft gel. Based on the viscosity of the toluene solution, the emulsion (silicone composition) had a structure represented by formula (B) with a molecular weight of approximately 250,000. Further, this emulsion was mixed with methyl methacrylate. LeThe silicone composition was graft-copolymerized with acrylic by dropwise addition of t-butyl hydroperoxide at 27°C over a period of 3-5 hours to obtain an emulsion of acrylic-silicone graft copolymer with a non-volatile content of 30%.
[0059] [Comparative Example 4] 160 g of the silicone emulsion obtained in Comparative Example 1 above and 75 g of the vinyl chloride emulsion obtained in Comparative Example 2 above were mixed with stirring for 1 hour to obtain a mixed emulsion with a non-volatile content of 42.7%.
[0060] The emulsions obtained in the above Examples 1 to 7 and Comparative Examples 1 to 4 were evaluated by the following methods. The results are shown in Tables 1 and 2.
[0061] <Solid content measurement method> Approximately 1 g of the sample was accurately weighed onto an aluminum foil dish, placed in a dryer maintained at approximately 105°C, heated for 1 hour, then removed from the dryer and allowed to cool in a desiccator. The aluminum foil dish containing the dried sample was weighed and the solid content (evaporation residue) was calculated using the following formula.
number
[0062] <Viscosity measurement method> The liquid temperature of the sample was kept at 23±0.5° C., and the viscosity was measured using a rotational viscometer (No. 1 rotor, 6 rpm, manufactured by Toki Sangyo Co., Ltd.: product name: VISCOMETER TVB-10).
[0063] <Average particle size> The average particle size was measured by weighing 0.01 g of the sample and using a laser diffraction particle size distribution analyzer (manufactured by Horiba, Ltd., product name: LA-950V2) under conditions of a circulation flow rate of 2 and agitation speed of 2 (the particle size value equivalent to 50% of the cumulative particle size distribution). [Measurement conditions] Measurement temperature: 25±1℃ Solvent: Ion-exchanged water
[0064] <Measurement of minimum film formation temperature (MFT)> The minimum film-forming temperature (MFT, °C) of the emulsion was measured by a method conforming to JIS K-6828-2. In detail, a simple film-forming temperature measuring device (manufactured by Imoto Manufacturing Co., Ltd.) was used, in which a heating source and a cooling source were installed at a certain distance. 1 μl of the emulsion was applied to aluminum foil, and the coating state after 2 hours was observed using the device. The emulsion was dried under a temperature gradient, and the boundary temperature between the transparent part where the film was formed and the part where the film was not formed was measured, and this was taken as the minimum film-forming temperature (MFT, °C). Considering the drying property during the formation of the coating, it is desirable for the MFT to be 100°C or less.
[0065] <Static and dynamic friction coefficient measurement> The emulsions of the respective Examples and Comparative Examples were applied to a PET film using a bar coater and dried at 105° C. for 3 minutes to form coatings having a thickness of about 10 μm after drying. A 200 g metal indenter was placed in contact with the coating film perpendicularly using a HEIDON TYPE-38 (manufactured by Shinto Scientific Co., Ltd.), and the frictional force was measured when the indenter was moved at 3 cm / min, and the friction coefficient was calculated from the frictional force. The preferred ranges for the static and kinetic friction coefficients under the above conditions are a static friction coefficient of 0.2 or less and a kinetic friction coefficient of 0.1 or less.
[0066] <Adhesion to substrate> Each of the emulsions of the Examples and Comparative Examples was applied to a soft polyvinyl chloride film using a bar coater and dried at 105° C. for 3 minutes to form a coating film having a thickness of about 10 μm after drying. Cellophane tape was applied to the coating film and then quickly peeled off, and the adhesion was evaluated visually. ○: No peeling from the substrate ×: Peeling from the substrate occurred
[0067] <Alcohol resistance> The emulsions of the respective Examples and Comparative Examples were applied to a PET film using a bar coater and dried at 105° C. for 3 minutes to form coatings having a thickness of about 10 μm after drying. 98% ethanol was dropped onto the coating film and it was air-dried at room temperature overnight. The change in the coating film after air-drying was evaluated visually. ○: No change in appearance △: Traces remain but no whitening ×: Whitening
[0068] <Water contact angle measurement> The emulsions of the respective Examples and Comparative Examples were applied to a PET film using a bar coater and dried at 105° C. for 3 minutes to form coatings having a thickness of about 10 μm after drying. 2 μl of pure water was dropped onto the coating film, and the contact angle values after 1 second and 30 seconds were measured using a contact angle meter CA-D model manufactured by Kyowa Interface Science Co., Ltd. Considering the prevention of water-based stains due to water repellency, the contact angle is preferably 80° or more.
[0069] [Table 1]
[0070] [Table 2]
Claims
1. A vinyl chloride-silicone graft copolymer which is a graft copolymer of (A) an organopolysiloxane represented by the following formula (1) and (B) vinyl chloride, wherein the mass ratio of said organopolysiloxane (A) to said vinyl chloride (B) is (A):(B)=5:95 to 95:
5. 【Chemistry 1】 (In formula (1), R 1 are the same or different substituted or unsubstituted monovalent hydrocarbon groups having 1 to 20 carbon atoms, R 2 is a radical reactive functional group. X is the same or different, substituted or unsubstituted, alkyl group having 1 to 20 carbon atoms, cycloalkyl group, aryl group, alkoxy group having 1 to 20 carbon atoms, or hydroxyl group. Y is X or -[O-Si(X) 2 ] d -X, which may be the same or different. Z is an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, or a hydroxyl group. a is a number from 0 to 10,000, b is a number from 1,000 to 10,000, c is a number from 0.0001 to 100, and d is a number from 1 to 1,000.
2. A method for producing a vinyl chloride-silicone graft copolymer, comprising the step of polymerizing (A) an organopolysiloxane represented by the following formula (1) with (B) vinyl chloride in a mass ratio of (A):(B) of 5:95 to 95:5: 【Chemistry 2】 (In formula (1), R 1 are the same or different substituted or unsubstituted monovalent hydrocarbon groups having 1 to 20 carbon atoms, R 2 is a radical reactive functional group. X is the same or different, substituted or unsubstituted, alkyl group having 1 to 20 carbon atoms, cycloalkyl group, aryl group, alkoxy group having 1 to 20 carbon atoms, or hydroxyl group. Y is X or -[O-Si(X) 2 ] d -X, which may be the same or different. Z is an alkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, or a hydroxyl group. a is a number from 0 to 10,000, b is a number from 1,000 to 10,000, c is a number from 0.0001 to 100, and d is a number from 1 to 1,000.
3. A composition comprising the vinyl chloride-silicone graft copolymer according to claim 1 in an amount of 10 to 60% by mass in terms of solid content based on the total mass of the composition.
4. 2. An emulsion of the vinyl chloride-silicone graft copolymer according to claim 1.
Citation Information
Patent Citations
Preparation method of silicon-containing core-shell structure vinyl chloride copolymers
CN108129613A
Production of vinyl chloride resin graft copolymer
JP1984166520A
Production of vinyl chloride copolymer
JP1986042519A
Silicone rubber graft polymer having notch impact strength
JP1988063710A
Polyorganosiloxane thermoplastic resin
JP1990008209A
Cited By
Vinyl chloride-silicone core-shell polymer and method for producing same
WO2026163870A1